Caracterização de progênies de alface quanto à tolerância ao vírus do mosaico do alface e ao nematóide das galhas e características agronômicas, em sistema orgânico - Silva, Sylmara (2018)
The production of organic food is a segment that is constantly expanding in the country, due to consumers demand for food produced in a more sustainable way. Among the foods produced by organic agriculture, lettuce (Lactuca sativa L.) stands out as the green leafy vegetable of the greatest economic importance for Brazil, besides having a great social importance, since it is widely cultivated by family farmers. However, there are no lettuce cultivars developed for this cultivation system. Among the desirable characteristics in a lettuce cultivar for organic agriculture, resistance to diseases, among them the root nematode (Meloidogyne incognita) and the Lettuce Mosaic Virus (LMV), as well as good agronomic characteristics, are noteworthy. In this context, the objective of this work was to characterize lettuce F2:4 progenies from the crosses between Salinas 88 and Colorado cultivars, in order to obtain suitable cultivars for organic agriculture. Three experiments were carried out. In the first one, in order to select LMV-resistant progenies, the manifestation of symptoms was evaluated from a scale of notes. Five progenies were selected to advance the breeding program, AFX 024D 1309 3306, AFX 024D 1241 3126, AFX 024D 1309 3487, AFX 024D 1228 3421 and AFX 024D 1211 3167. In the second experiment, to select progenies resistant to the root nematode, the number of eggs, the reproduction index, the reproduction factor and the incidence of galls were evaluated. Progenies AFX 024D 1309 3487, AFX 024D 1351 3404, AFX 024D 118 13182, AFX 024D 1309 3306 and AFX 024D 1241 3277 were selected to advance the breeding program for resistance to the root nematode. In both trials the progenies AFX 024D 1309 3306 and AFX 024D 1309 3487, stood out from the others, being selected for both characteristics. In the third experiment was aimed to characterize progenies, aiming to identify promising materials that presented desirable phenotypic characteristics in relation to leaf types, early flowering and seed production. It was verified that there is a great genetic variability for agronomic characteristics evaluated, being necessary the advance of the generations to identify materials with desirable commercial characteristics. Heritability values were high in both trials, increasing the possibility of genetic gains with selection.